A Novel Intimate Partner Violence Curriculum for Internal Medicine Residents: Development, Implementation, and Evaluation - Emily R. Insetta; Colleen Christmas (Association of American Medical Colleges, 2020)
Introduction Intimate partner violence (IPV) is a prevalent problem with profound health consequences. Research suggests that internal medicine (IM) residents are unprepared to screen for and address IPV. We designed a curriculum to improve IM residents' knowledge, attitudes, and practices in caring for IPV survivors. Methods The curriculum was delivered to first-year IM residents from 2016 to 2017 at Johns Hopkins Bayview. Part 1 was 60 minutes long, with a video, evidence-based didactic teaching, and case-based discussion. Part 2 was 90 minutes long, with evidence-based didactic teaching, role-play of patient-provider conversations about IPV, and debriefing about strategies for discussing IPV. We evaluated knowledge, confidence, and self-reported behaviors pre- and postintervention using two-tailed paired t tests. Results Thirty-two residents received IPV training. In comparing precurriculum (n = 29, 91% of total participants) and postcurriculum (n = 28, 88% of total participants) surveys, there was significant improvement in knowledge about IPV (p < .001). Postcurriculum, learners reported greater confidence in detecting IPV (p < .001), documenting IPV (p < .001), and referring to resources (p < .001). Participants reported increased comfort with managing difficult emotions about IPV in patients (p < .01) and themselves (p < .001) and increased comfort in discussing IPV with female (p < .001) and male (p < .001) patients. Postcurriculum, all respondents felt they were more skillful in discussing IPV and would be more likely to screen for IPV. Discussion Our curriculum improved residents' knowledge, confidence, comfort, and preparedness in screening for and discussing IPV.